2023
DOI: 10.1159/000527582
|View full text |Cite
|
Sign up to set email alerts
|

Renal Autologous Cell Therapy in Type 2 Diabetes with Late Stage 4 Diabetes-Related Chronic Kidney Disease: Trial Design and Early Analysis

Abstract: <b><i>Introduction:</i></b> Cell-based therapies potentially delay the trajectory toward end-stage kidney disease (ESKD) in late stage 4 diabetic chronic kidney disease (DKD). We describe the trial design, baseline patient characteristics, and early results of an IRB-approved phase II multicenter clinical trial, utilizing Renal Autologous Cell Therapy (REACT) in adults with pre-ESKD due to type 2 DKD. The trial objectives were safety and tolerability of REACT by assessment of the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Histologic analysis comparing treated to untreated kidneys in a nephrectomy CKD model indicated significantly reduced glomerular sclerosis and tubulointerstitial injury at 24 weeks post-injection [ 9 ]. Interim results in early-phase open-label trials with up to two rilparencel doses in a single kidney at prescribed intervals demonstrated an improved eGFR slope between pre- and post-treatment injections, supporting preservation of function [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histologic analysis comparing treated to untreated kidneys in a nephrectomy CKD model indicated significantly reduced glomerular sclerosis and tubulointerstitial injury at 24 weeks post-injection [ 9 ]. Interim results in early-phase open-label trials with up to two rilparencel doses in a single kidney at prescribed intervals demonstrated an improved eGFR slope between pre- and post-treatment injections, supporting preservation of function [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%